The Turkish Pain Catastrophizing Scale-Child in Adolescents with Familial Mediterranean Fever: A Psychometric Analysis - Devrim Can Sarac; Deniz Bayraktar; Ozge Altug Gucenmez; Balahan Bora; Sema Savci; Sevket Erbil Unsal (Archives of Rheumatology, 2025)
Background/Aims: No validated method exists to assess pain catastrophizing in adolescents with FMF. We evaluated validity and reliability of the Turkish Pain Catastrophizing Scale-Child (PCS-C) by examining internal consistency, test-retest reliability, and convergent validity. Materials and Methods: PCS-C, VAS-rest, VAS-activity, and PedsQL Arthritis Module 3.0 were administered to 66 adolescents with FMF (13–18 years). Cronbach’s alpha measured internal consistency. PCS-C was re-administered 2 weeks later to 24 participants to calculate ICC for test-retest reliability. Convergent validity was assessed via Spearman correlations with other parameters. Results: Item 8 was excluded for low consistency. Cronbach’s alpha = 0.934. Remaining items correlated item-total > 0.4; alpha change < 1% if any item removed. Test-retest reliability ICC = 0.925. PCS-C scores correlated with VAS-rest (r_s = 0.373), VAS-activity (r_s = 0.536), and PedsQL (r_s = 0.551). Conclusion: Turkish PCS-C is a valid and reliable tool for assessing pain catastrophizing in adolescents with FMF.